Synthesized zirconia powder from Australian zircon sand: article - Mohsin, Mimi Fazzlinda; Subuki, Istikamah (2019)
Zirconia (ZrO₂) is one of the bioceramic materials widely used in dental restorations in surgical applications. The Zirconia powder is synthesized using Australian zircon sand using the alkali fusion method at 500°C, 600°C, 700°C and 800°C of calcination temperature. The synthesized Zirconia are being analysed using X-Ray Diffractometer (XRD), particle size distribution, Scanning Electron Microscopy (SEM) and Brunauer–Emmett–Teller (BET). The results showed that synthesized zirconia are monoclinic phases and the surface area of the synthesized zirconia based on the calcination temperature for 500°C, 600°C, 700°C and 800°C are 0.0635 m² /g, 0.135 m² /g, 0.0268 m² /g and 0.0288 m² /g. For BET surface area are 1.0721 m² /g, 0.6811 m² /g, 1.8915 m² /g and 1.5074 m² /g. Based on SEM images, the surface structure of the powder has been determined and at zirconia that been calcined at 600°C showed the similarity with commercial zirconia. Due to the structure of zirconia are not stabilized, dopant zirconia with yttrium oxide (Y₂O₃) is done using ball milling to produce 3 mole % yttria stabilized zirconia (YSZ). The several tetragonal structure is determined in 3 mole % YSZ. The similarities of synthesized zirconia and commercial zirconia showed that the synthesized of zirconia powder from zircon sand is successful.